Local Wisdom and Biodiversity on Mushrooms Folk at the KhaoKra-dong Volcano Forest Park on Samed Sub District, Muang District, Buriram Province - แสนสุข, เทพอัปสร (KKU Science Journal, 2017)
This research were survey on the diversity of macro-fungi at KhaoKra-dong Volcano Forest Park on Samed Sub District, Muang District, Buriram Province during May – September 2015. The macro-fungi were collected and morphologically identified by comparing of their macro-characteristics with manual of identification book. The results revealed that 25 species belongs to 10 families were obtained. Among fungal taxa, they were classified as 5 groups including 1) gilled fungi, 2) boletes fungi, 3) polypores fungi, 4) coral fungi, and 5) puffballs fungi. Subsequently, edible mushrooms was discriminated which mostly found in family Russulaceae, including Russula emetic, Russula alboareolata, Russulaceae cyanoxantha, Rusula viresceus Fr, Lactarius hygrophoroides, and Lactarius glaucescens, the second most was Pluteaceae such as Ganoderma lucidum, Lentinus polychrous, Lentinus squarrosulas Mont., and Lentinus strigoeue (Schw) Fr. Additionally, inedible mushroom or poisonous mushroom was found to be Pluteaceae (Amanita sp.). For study of local wisdom and utilization guideline in the villager of these mushroom, it was found local knowledge relationship between mushroom and the way of living several aspects. Most of villagers have been collecting these mushrooms for their trade and foods. By inherited the local wisdom to know the natural mushrooms source, to know the features of mushrooms, to know the method of collecting wild mushrooms, to know the method of classification wild mushrooms, to know how to pick mushrooms, edible and inedible mushrooms on a belief in collecting wild mushrooms. Include ways to exploit wild mushrooms in different ways by observing familiar experiences, watching adults, collecting mushrooms, and inquiring from the elders. The knowledge derived from indigenous knowledge can be passed on from generation to generation in the exploitation and gathering wild mushrooms.